Empirically Supported Treatments for Students with Autism: General Education Teacher Knowledge, Use, and Social Validity Ratings. (18th August 2019) - Sulek, Rhylee; Trembath, David; Paynter, Jessica; Keen, Deb
ABSTRACT: Objective : To examine teachers' knowledge and use of empirically supported treatments (ESTs) for children with autism spectrum disorder (ASD), and the extent to which they deem them socially valid in general education settings. Method : Totally, 155 general education teachers completed an online survey examining knowledge, use, and perceived social validity of ESTs targeting school readiness skills. Sources of information accessed and the relationship of knowledge, use, and social validity with demographic variables were investigated. Results : Teachers reported knowledge of, and were using, all ESTs. ESTs were used more frequently than non-ESTs. Knowledge, use, and social validity of ESTs were strongly associated. Teachers reported accessing a range of sources of information, with varying degrees of trust placed in these sources. Conclusion : Teachers' knowledge of available ESTs for children with ASD is linked to their use. Increasing awareness of social validity of ESTs, and how they can be successfully translated into classroom settings will influence uptake.